2016
DOI: 10.1242/jcs.176149
|View full text |Cite
|
Sign up to set email alerts
|

Uses and abuses of macropinocytosis

Abstract: Macropinocytosis is a means by which eukaryotic cells ingest extracellular liquid and dissolved molecules. It is widely conserved amongst cells that can take on amoeboid form and, therefore, appears to be an ancient feature that can be traced back to an early stage of evolution. Recent advances have highlighted how this endocytic process can be subverted during pathology -certain cancer cells use macropinocytosis to feed on extracellular protein, and many viruses and bacteria use it to enter host cells. Prion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
179
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(184 citation statements)
references
References 110 publications
5
179
0
Order By: Relevance
“…Nevertheless, both processes share many similarities and components because, in both cases, the dynamic assembly of actin filaments together with myosins generates forces that drive internalization of fluid or large particles. Moreover, they are of high medical relevance because, in the immune defense, phagocytosis is a major mechanism to remove pathogens (7), whereas many cancer cells thrive by excessive macropinocytosis (3,5). Recent work with Dictyostelium showed that the nucleation-promoting factor SCAR/WAVE localizes at the very rim of macropinosomes, suggesting that the Arp2/3 complex acts as a potent nucleator of the underlying actin filament network (38).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, both processes share many similarities and components because, in both cases, the dynamic assembly of actin filaments together with myosins generates forces that drive internalization of fluid or large particles. Moreover, they are of high medical relevance because, in the immune defense, phagocytosis is a major mechanism to remove pathogens (7), whereas many cancer cells thrive by excessive macropinocytosis (3,5). Recent work with Dictyostelium showed that the nucleation-promoting factor SCAR/WAVE localizes at the very rim of macropinosomes, suggesting that the Arp2/3 complex acts as a potent nucleator of the underlying actin filament network (38).…”
Section: Resultsmentioning
confidence: 99%
“…In higher eukaryotes, as exemplified by neutrophils and macrophages, phagocytosis is a central part of the innate immune system responsible for the clearance of viral and bacterial pathogens (2), whereas the scavenging of nutrients and metabolites by macropinocytosis is considered increasingly important for tumor progression and cancer cell proliferation (3)(4)(5). Phagocytosis and macropinocytosis are actin-driven processes that entail rearrangements of the plasma membrane to engulf extracellular material, followed by delivery of the ingested material into lysosomes for extraction of nutrients (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sustained proliferation requires a metabolic reprogramming, which includes the internalization of carbon sources and amino acids from the interstitial fluid by macropinocytosis (Bloomfield and Kay, 2016). Ras mutants have been known to upregulate macropinocytosis and septins were recently found to affect the intracellular transport of macropinosomes in a dose dependent manner (Bryant et al, 2014; Dolat and Spiliotis, 2016).…”
Section: Emerging Roles Of Septins In Cancermentioning
confidence: 99%
“…The fluids are internalized according to the fusion of the membranous protrusions by themselves [24]. Ras, PI3K, Src and Rac1 activities have been shown to stimulate macropinocytosis [25,26,27,28,29]. Since Ras was upregulated in T24 cells in this study, it is possible that the Ras upregulation coordinately stimulated macropinocytosis with Dkk-3 and Rab5 [30].…”
Section: Discussionmentioning
confidence: 97%